SOLAR AND WIND ENERGY: A CASE STUDY OF THE ALTAI KRAI - E. S. Ushakov (Siberian Journal of Tourism and Economic, 2018)
The limited nature of natural resources and the increasing complexity of the extraction of fossil fuels, combined with global environmental pollution, are pushing humankind to search for renewable alternative energy sources. Together with the reduction of harm to the environment from new energy resources, this will bring the reduction to the minimum cost of all cycles of transportation, processing and production. The article provides an overview of the development of alternative energy sources in the world. Considered the largest sources of alternative 102 energy: solar energy and wind energy, which can be used in the area. The analysis of the state and identified prospects for the development of alternative energy in the region under consideration.